Variation of body temperature after sponge bath in stable very low birth weight preterm neonates - Mangalgi, Sharanabasavesh; Upadhya, Namratha (Indian Journal of Child Health, 2022)
Aim: To observe the variation of the body temperature after routine sponge bath in stable very low birth weight preterm babies. Methods: 74 babies admitted to the neonatal intensive care unit (NICU) of a tertiary care teaching hospital were enrolled. The inclusion criteria were babies with corrected gestational age between 28 and 36 weeks, birth weight <1500 g during postnatal age of 14-28 days who were stable, on full feeds. All babies were in incubator at preset temperature. The babies received sponge bath within the incubator as a part of developmental care by a trained nurse. The axillary temperatures before bath and at 15, 30 and 60 min post bath were measured. The mean differences between the temperature before bath and after bath were analyzed using repeated measures analysis of variance. A p<0.05 was considered significant. Results: None of the babies receiving sponge bath developed hypothermia. There was a drop in the axillary temperature at 15 min post bath as compared to the temperature before bath (p=0.00, mean difference=?0.174°F, 95% confidence interval=0.119-0.229). Subsequently, there was a rise in temperature at 30 min and the temperature normalized by 60 min after bath. The differences in temperature before and 15 min post bath were uniformly significant across all weight groups. Conclusion: Routine sponge bath in stable preterm babies causes a transient drop in temperature but does not lead to hypothermia. As it is a relatively simple technique and incorporates developmental care, it can be used as a part of routine care of stable preterm babies.